Application of Sulfated Tin (IV) Oxide Solid Superacid Catalyst to Partial Coupling Reaction of α-Pinene to Produce Less Viscous High-Density Fuel - Seong-Min Cho; Chang-Young Hong; Se-Yeong Park; Da-Song Lee; June-Ho Choi; Bonwook Koo; In-Gyu Choi (Energies, 2019)
Brønsted acid-catalyzed reactions of α-pinene have been studied because of their ability to produce various types of fragrance molecules. Beyond this application, dimeric hydrocarbon products produced from coupling reactions of α-pinene have been suggested as renewable high-density fuel molecules. In this context, this paper presents the application of a sulfated tin(IV) oxide catalyst for the partial coupling reaction of α-pinene from turpentine. Brønsted acid sites inherent in this solid superacid catalyst calcined at 550 °C successfully catalyzed the reaction, giving the largest yield of dimeric products (49.6%) at 120 °C over a reaction time of 4 h. Given that the low-temperature viscosity of the mentioned dimeric products is too high for their use as a fuel in transportation engines, lowering the viscosity is an important avenue of study. Therefore, our partial coupling reaction of α-pinene provides a possible solution as a considerable amount of the isomers of α-pinene still remained after the reaction, which reduces the low-temperature viscosity. On the basis of a comparison of the reaction products, a plausible mechanism for the reaction involving coinstantaneous isomerization and coupling reaction of α-pinene was elucidated.